Answer:
3
Step-by-step explanation:
(f O g) this basically means that the input x first goes trough the function g and then f. Like f(g(x)).
So when x went trough g, you got the output g(x) and then this went trough f and you got f(g(x)) = -8 = 'f(x)'.
With this in mind you can retrace your steps by first looking at what input can get -8 as an output, for f this is -4. this means g(x) = -4
Then you look at what input (this is the x you're looking for) gets you the ouput -4. Looking at the second image you'll picture see that it's the input 3.
We have been given the expression
![x^{\frac{9}{7}}](https://tex.z-dn.net/?f=x%5E%7B%5Cfrac%7B9%7D%7B7%7D%7D)
We have the exponent rule
![x^{\frac{a}{b}}= x^{a^{(\frac{1}{b})}}](https://tex.z-dn.net/?f=x%5E%7B%5Cfrac%7Ba%7D%7Bb%7D%7D%3D%20x%5E%7Ba%5E%7B%28%5Cfrac%7B1%7D%7Bb%7D%29%7D%7D)
Using this rule, we have
![x^{\frac{9}{7}}= x^{9^{(\frac{1}{7})}}](https://tex.z-dn.net/?f=x%5E%7B%5Cfrac%7B9%7D%7B7%7D%7D%3D%20x%5E%7B9%5E%7B%28%5Cfrac%7B1%7D%7B7%7D%29%7D%7D)
Now, using the fact that
, we get
![x^{\frac{9}{7}}= \sqrt[7]{x^9}\\ \\ x^{\frac{9}{7}}=\sqrt[7]{x^7\times x^2}\\ \\ x^{\frac{9}{7}}=x\sqrt[7]{x^2}](https://tex.z-dn.net/?f=x%5E%7B%5Cfrac%7B9%7D%7B7%7D%7D%3D%20%5Csqrt%5B7%5D%7Bx%5E9%7D%5C%5C%0A%5C%5C%0Ax%5E%7B%5Cfrac%7B9%7D%7B7%7D%7D%3D%5Csqrt%5B7%5D%7Bx%5E7%5Ctimes%20x%5E2%7D%5C%5C%0A%5C%5C%0Ax%5E%7B%5Cfrac%7B9%7D%7B7%7D%7D%3Dx%5Csqrt%5B7%5D%7Bx%5E2%7D)
D is the correct option.
Answer:
0.075 metre
2000 mm
500 cm
0.001 gram
1.5 × 10-6 kilogram
86400 second
18000 second
Step-by-step explanation:
hope it helps
Answer:
10/10
Step-by-step explanation: